Alternative classifications of mechanisms producing annual maximum wind gusts in Resistencia and Corrientes, Argentina - Palese, Claudia; Natalini, Bruno (Journal of wind engineering and industrial aerodynamics, 2023)
Assessment methods for wind loads on buildings and civil structures require the statistical processing of extreme wind speeds. If the wind climate is mixed, there is ample consensus that statistical models appropriate for mixed climate must be applied. This is not always possible because most of the models in use entail separating wind speeds according to the meteorological mechanism causing it. As classification of wind speed records is an expensive task, quantitative information on this subject is scarce. Here, annual maximum wind gusts recorded in the meteorological stations of the Resistencia and Corrientes airports, Argentina, are classified according to the mechanisms that produced them. Three alternative separation criteria were applied: (i) thunderstorm vs. other mechanism; (ii) synoptic vs. non-synoptic; and (iii) convective storms vs. those that were associated with the passage of a cold front. The available data sets were the Daily Registers of the stations from 1968 to 2016. The data series were conditioned to generate a single superstation series. The results show that the annual maximum gust produced by thunderstorms has an occurrence of 97.2% compared to other mechanisms; 93.1% correspond to non-synoptic wind; and 62.5% were classified as convection not associated with the passage of a cold front. It is concluded that Corrientes and Resistencia are not subject to mixed extreme wind climate, that is, the maximum annual gust is due to a simple wind climate corresponding to intense convective activity. •Classification of storms in two cities of Argentina is presented.•Three different classification criteria have been tried.•Results show that extreme wind climate in the area of study is not mixed.•It is dominated by convective storms of which roughly a third is associated with passing cold fronts.